1974
DOI: 10.1172/jci107709
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary Function in Diverse Hyperprolactinemic States

Abstract: A B S T R A C T Prolactin secretion in normal adults is characterized by periods of episodic secretion which increase in magnitude during sleep. In this study, we report the 24-h mean prolactin concentrations, prolactin secretory patterns, and associated pituitary hormone function in nine patients (seven women and two men) with hyperprolactinemia of diverse etiologies. Four of the women and one of the men had clinically demonstrable pituitary tumors, one boy had a hypothalamic tumor, and the three other women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

1976
1976
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(41 citation statements)
references
References 51 publications
2
37
0
2
Order By: Relevance
“…Sleep changes are thought to affect neuroendocrine function related to testosterone secretion. Boyar et al, 1974 have reported that testosterone increases the LH production during sleep in early and mid-puberty. Sleep apnea appears to be an independent predictor for low testosterone levels in severely obese men (Hammoud et al, 2011).…”
Section: Sleep Disorders In Obese Infertile Malesmentioning
confidence: 99%
“…Sleep changes are thought to affect neuroendocrine function related to testosterone secretion. Boyar et al, 1974 have reported that testosterone increases the LH production during sleep in early and mid-puberty. Sleep apnea appears to be an independent predictor for low testosterone levels in severely obese men (Hammoud et al, 2011).…”
Section: Sleep Disorders In Obese Infertile Malesmentioning
confidence: 99%
“…It became possible to demonstrate elevated blood prolactin levels not only in cases of Forbes-Albright syndrome but also in an appreciable number of "clinically nonfunctioning" chromophobe adenomas (Boyar et al, 1974;Tolis et al, 1974;Zimmerman et al, 1974). Prolactin secreting tumors are more common than was previously assumed and as many as 20-25 per cent of all pituitary adenomas might arise from prolactin cells.…”
Section: Prolactin-cellmentioning
confidence: 99%
“…Excessive PRL might also act at the hypothalamic level to interfere with spontaneous episodic gonadotropin release (Boyar et al, 1974;Bohnet et al, 1976) and inhibit the normal positive feedback effect of estrogen on gonadotropin secretion (Glass et al, 1975;Faglia et al, 1977;Aono et al, 1979). In addition, L'Hermite and coworkers (1978) have reported that hyperprolactinemia induced experimentally by sulpiride administration is associated with an impaired positive estrogen feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%